Optimized high performance liquid chromatography-ultraviolet detection method using core-shell particles for the therapeutic monitoring of methotrexate - Montemurro, Milagros (2016)
Methotrexate (MTX) is an antineoplastic drug, and due to its high toxicity, the therapeutic drug monitoring is strictly conducted in the clinical practice. The chemometric optimization and validation of a high performance liquid chromatography (HPLC) method using core-shell particles is presented for the determination of MTX in plasma during therapeutic monitoring. Experimental design and response surface methodology (RSM) were applied for the optimization of the chromatographic system and the analyte extraction step. A Poroshell 120 EC-C18 (3.0 mm×75 mm, 2.7 μm) column was used to obtain a fast and efficient separation in a complete run time of 4 min. The optimum conditions for the chromatographic system resulted in a mobile phase consisting of acetic acid/sodium acetate buffer solution (85.0 mM, pH=4.00) and 11.2% of acetonitrile at a flow rate of 0.4 mL/min. Selectivity, linearity, accuracy and precision were demonstrated in a range of 0.10-6.0 μM of MTX. The application of the optimized method required only 150 μL of patient plasma and a low consumption of solvent to provide rapid results.